Cost-Utility Analysis of Add-on Cannabidiol vs Usual Care Alone for the Treatment of Seizures in Patients With Treatment-Resistant Lennox-Gastaut Syndrome or Dravet Syndrome in the Netherlands - Jamshaed Siddiqui; Sally Bowditch (Journal of Health Economics and Outcomes Research)
**Background:** Lennox-Gastaut syndrome (LGS) and Dravet syndrome (DS) are severe, treatment-refractory, epileptic encephalopathies that often develop in infancy or early childhood. Since December 1, 2022, plant-derived highly purified cannabidiol (CBD) medicine (Epidyolex®; 100 mg/mL oral solution) has been reimbursed in the Netherlands for the adjunctive treatment of seizures associated with LGS or DS. **Objective:** To estimate the cost-effectiveness of CBD plus usual care vs usual care alone in patients with LGS or DS in the Netherlands. **Methods:** A cohort-based Markov model from a Dutch societal perspective, based on seizure frequency and seizure-free days, was developed for patients receiving CBD plus usual care (antiseizure medications, including clobazam) or usual care alone. Population characteristics, clinical inputs, and utility values were sourced from CBD clinical trials and quality-of-life studies. Drug acquisition, disease management, adverse events, and societal costs from published literature were included. A 2019/2020 price year in euros was used. The model used a mean dosage of 12 mg/kg/day, a lifetime (90-year) horizon, and a 3-month cycle length. Discount rates of 4.0% and 1.5% per annum were applied to costs and outcomes, respectively. Uncertainty was explored through deterministic and probabilistic sensitivity analyses. **Results:** In patients with LGS, CBD plus usual care led to additional costs of €28 338 and increased quality-adjusted life-years (QALYs) of 1.318 compared with usual care alone. The incremental cost-effectiveness ratio of €21 493/QALY in LGS is below the willingness-to-pay threshold of €80 000/QALY in the Netherlands. In patients with DS, CBD plus usual care dominated usual care alone, with cost savings of €23 642 and increased QALYs of 0.868. The probability that CBD plus usual care is cost-effective in the Netherlands compared with usual care alone is 96% and 99% in patients with LGS and DS, respectively. **Discussion:** Elicitation methods were used to address data gaps in model inputs (eg, healthcare resource utilization and utilities); Dutch clinical experts, sensitivity, and scenario analyses validated this approach. **Conclusions:** Based on a willingness-to-pay threshold of €80 000, the base case cost-utility analysis demonstrated the cost-effectiveness of CBD plus usual care in patients with treatment-refractory LGS or DS aged 2 years or older in the Netherlands.